RELIGIOUS MODERATION IN A MULTICULTURAL SOCIETY IN THE AGE OF TECHNOLOGY AND INDUSTRY - Sri, Ayub Rohadi; Ardhya G, Sri Wurini (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2025)
Religious moderation is a concept that prioritizes balance in carrying out religious beliefs in society. Today, technological and industrial developments have created a new landscape in social interaction, which affects the religious diversity of society. Information technology, especially social media, allows individuals to disseminate religious views easily, both moderate and extreme. However, this development also poses challenges, especially in maintaining the values of tolerance and harmony between religious communities. This article explores the importance of religious moderation in a multicultural society and the impact of technological and industrial developments on people's religious practices. With a qualitative approach, this study examines the main issues that affect the implementation of religious moderation in the digital and industrial era. The results of this research are expected to provide insight for policymakers, religious leaders, and the wider community in realizing a harmonious life. The implication of this research is to enrich interdisciplinary studies between the study of religion, sociology, and technology. The concept of religious moderation raised in the context of multicultural society and technological advances contributes to a new understanding of the dynamics of religion in the digital era, especially in analyzing changes in interaction patterns, the spread of religious values, and the challenges of digital radicalism. In addition, it is also a strengthening of the values of religious moderation that can be an important foundation in creating social harmony in the midst of (SARA). In a society that is increasingly connected through technology, mutual respect and tolerance between religions must be strengthened to prevent conflict and social disintegration.